MDRD or CKD-EPI for glomerular filtration rate estimation in living kidney donors - Carla Burballa; Marta Crespo; Dolores Redondo-PachÃ³n; MarÃa JosÃ© PÃ©rez-SÃ¡ez; Marisa Mir; Carlos Arias-Cabrales; Albert FrancÃ©s; Lluis FumadÃ³; Lluis Cecchini; Julio Pascual (Nefrología (English Edition), 2018)
Introduction: The evaluation of the measured Glomerular Filtration Rate (mGFR) or estimated Glomerular Filtration Rate (eGFR) is key in the proper assessment of the renal function of potential kidney donors. We aim to study the correlation between glomerular filtration rate estimation equations and the measured methods for determining renal function. Material and methods: We analyzed the relationship between baseline GFR values measured by Tc-99m-DTPA (diethylene-triamine-pentaacetate) and those estimated by the four-variable Modification of Diet in Renal Disease (MDRD4) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations in a series of living donors at our institution. Results: We included 64 donors (70.6% females; mean age 48.3Â Â±Â 11 years). Baseline creatinine was 0.8Â Â±Â 0.1Â mg/dl and it was 1.1Â Â±Â 0.2Â mg/dl one year after donation. The equations underestimated GFR when measured by Tc99m-DTPA (MDRD4 â 9.4Â Â±Â 25Â ml/min, PÂ <Â .05, and CKD-EPI â 4.4Â Â±Â 21Â ml/min). The correlation between estimation equations and the measured method was superior for CKD-EPI (rÂ =Â .41; PÂ <Â .004) than for MDRD4 (rÂ =Â .27; PÂ <Â .05). eGFR decreased to 59.6Â Â±Â 11 (MDRD4) and 66.2Â Â±Â 14Â ml/min (CKD-EPI) one year after donation. This means a mean eGFR reduction of 28.2Â Â±Â 16.7Â ml/min (MDRD4) and 27.31Â Â±Â 14.4Â ml/min (CKD-EPI) at one year. Conclusions: In our experience, CKD-EPI is the equation that better correlates with mGFR-Tc99m-DTPA when assessing renal function for donor screening purposes. Resumen: IntroducciÃ³n: El estudio del filtrado glomerular medido (FGm) o del estimado (FGe) es el eje de la evaluaciÃ³n adecuada de la funciÃ³n renal en la valoraciÃ³n de un potencial donante vivo renal. Nos planteamos estudiar la correlaciÃ³n entre las fÃ³rmulas de estimaciÃ³n del FG y los mÃ©todos de mediciÃ³n para determinar la funciÃ³n renal. Material y mÃ©todos: Analizamos la relaciÃ³n entre los valores basales de FGm con Tc-99m-DTPA (dietilenolene-triamino-pentaacetato) y aquellos estimados mediante las fÃ³rmulas Modification Diet Renal Disease de 4 variables (MDRD4) y Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) en una serie de donantes vivos de nuestra instituciÃ³n. Resultados: Incluimos a 64 donantes (70,6% mujeres; con una edad media de 48,3Â Â±Â 11 aÃ±os). La creatinina basal fue 0,8Â Â±Â 0,1Â  y 1,1Â Â±Â 0,2Â mg/dl un aÃ±o posdonaciÃ³n. Las ecuaciones infraestiman el FG medido por Tc99m-DTPA (MDRD4 â9,4Â Â±Â 25Â ml/min y pÂ <Â 0,05; CKD-EPI â4,4Â Â±Â 21Â ml/min). La correlaciÃ³n entre las fÃ³rmulas estimativas y el mÃ©todo medido fue superior para CKD-EPI (rÂ =Â 0,41; pÂ =Â 0,004) que para MDRD4 (rÂ =Â 0,27; pÂ =Â 0,05). El FGe se redujo a 59,6Â Â±Â 11 (MDRD4) y a 66,2Â Â±Â 14Â ml/min (CKD-EPI) al aÃ±o posdonaciÃ³n. Esto supone una reducciÃ³n media del FGe de 28,2Â Â±Â 16,7Â ml/min (MDRD4) y de 27,31Â Â±Â 14,4Â ml/min (CKD-EPI) al aÃ±o. ConclusiÃ³n: En nuestra experiencia, CKD-EPI es la fÃ³rmula que mejor se correlaciona con el FGm-Tc99m-DTPA en la evaluaciÃ³n de la funciÃ³n renal para el cribado de donantes. Keywords: Glomerular filtration rate, CKD-EPI, MDRD4, Tc99m-DTPA, Living kidney donor, Palabras clave: Filtrado glomerular, CKD-EPI, MDRD4, Tc99m-DTPA, Donante renal vivo